Job Satisfaction as a Mediator in the Relationship Between Leadership, Organizational Support and Work Motivation - Yakup Yakup; Roydah Gani; Idrus Usu; Nurnaningsih Utiarahman (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Gender has become an important issue in the workplace, especially related to its influence on job satisfaction and motivation. This study aims to analyze the influence of leadership, organizational support, compensation, and gender on job motivation, with job satisfaction as a mediating variable. This study was conducted on employees of the Muara Tirta Gorontalo Regional Water Company with a quantitative approach and explanatory design. Data were obtained from 145 respondents who were purposively selected from 609 employees, using a closed questionnaire based on a five-point Likert scale. The analysis was carried out using the path analysis method with the help of Lisrel 8.7 software. The results of the study showed that leadership, organizational support, compensation, and gender had a significant effect on job satisfaction, which then partially mediated the effect on work motivation. Fair gender treatment has been shown to reduce inequality and increase motivation. Compensation and leadership are dominant factors in shaping job satisfaction and motivation. These findings support the Social Exchange Theory which emphasizes the importance of reciprocal relationships between organizations and employees. Practically, the results of this study encourage public sector organizations to implement justice-based policies, effective leadership, and transparent compensation systems to increase work motivation.